The Effects of Ring Expansion and N‐Methylation on the Complexation Behaviour of Macrodinucleating Hexaaza‐Dithiophenolate Macrocycles: Destabilization of the CoIII Oxidation Level and Lowering of the Coordination Number. Issue 8 (10th January 2013) - Lehmann, Ulrike; Lach, Jochen; Schleife, Frederik; Jeremies, Alexander; Kersting, Berthold
Abstract: The preparation and characterization of 30‐membered hexaza‐dithiophenolate macrocycles H2 L 4 –H2 L 6 with different degrees and patterns of N ‐alkylation and their complexation properties towards cobalt are reported. Three dinuclear {[Co III 2 (L 4 )(µ‐OH)] 3+ (3 ), [Co III Co II (L 5 )(µ‐OH)] 2+ (4 ), [Co II 2 H2 (L 6 )Cl2 ] 2+ (5 )} and one mononuclear complex {[Co II (L 6 )] 2+ (6 )} were obtained, isolated as ClO4 – or BPh4 – salts, and characterized by CHN analysis, ESI mass spetrometry, IR, UV/Vis, and NMR spectroscopy, cyclic voltammetry, magnetic susceptibility measurements (for4 –6 ), and X‐ray crystallography (3 –6 ). In contrast to parent N6 S2 macrocycles with diethylenetriamine linkers, which support only face‐sharing bioctahedral [Co2 L(L′)] n + complexes (L′ = bridging coligand), the new macrocycles show greater structural diversity enabling the formation of triply bridged complexes with octahedral Co III, II N3 S2 O (3, 4 ), non‐bridged dinuclear complexes with tetrahedral Co II N2 SCl (5 ), and mononuclear complexes with square‐pyramidal Co II N3 S2 (6 ) coordination environments. The increasing stability of the Co II oxidation level across this series of complexes is a consequence of the increasing degree of N ‐alkylation coupled with a decreasing ligand‐field strength of the tertiary amine functions, as demonstrated by significant anodic shifts in the cyclic voltammograms of3 and4 . The effective magnetic moments of the Co II ions in4, 5, and6 (4.67–5.23 µB ) are significantly higher than the expected spin‐only value of 3.87 µB, indicative of an orbital contribution to the magnetic moment. Abstract : Three new hexaaza‐dithiophenolate N6 S2 macrocycles (H2 L 4 –H2 L 6 ) have been prepared and their coordination properties towards cobalt examined. Greater flexibility and structural diversity relative to parent N6 S2 macrocycles are trademarks of the new macrocycles. These macrocycles also readily convert Co III to lower‐coordination Co II compounds as established by X‐ray crystallography.